The Flouting of Grice’s Cooperative Maxims in the Dialogues in Pearls before Swine Web Comic - Fauziah, Rizka; Yuliasri, Issy; Rukmini, Dwi (English Education Journal, 2020)
Web comic is one of media of communication that can attract both children and adults. It may contain humor. Humor itself may be created by flouting the cooperative principles. This study aimed to explore the types of maxims flouting of Grice’s maxims in Pearls before Swine web comic and their contributions to create humor in the comic. This study was descriptive qualitative research in the form of discourse analysis. 30 episodes of the comic were used as data. The data were then collected and analyzed under three big steps proposed by Miles and Huberman (1994, p. 10). The results of the study revealed that all types of maxims were flouted in web comic. The most prominent flouting was the flouting of relevance maxim, then followed by the flouting of quantity maxim, manner maxim, and quality maxim became the least maxim that was flouted. Maxim of quality contributed to create humor as in the flouting there were sarcastic words which were intentionally used to trigger funny situation. The use of flouting of quantity maxim was indicated on the use of exaggeration which enhanced the information and blown thing up beyond the response needed. Relevance maxim was flouted by using both facetiousness and repartee. Meanwhile, in the flouting of manner maxim, the contributions were on the use of insult and pun.